Lactobacillus plantarum PL-02 Supplementation Combined With Resistance Training Improved Muscle Mass, Force, and Exercise Performance in Mice - Yeh, Wen-Ling; Hsu, Yi-Ju; Ho, Chin-Shen; Ho, Hsieh-Hsun; Kuo, Yi-Wei; Tsai, Shin-Yu; Huang, Chi-Chang; Lee, Mon-Chien (Frontiers in Nutrition, 2022)
Increasing numbers of researchers are investigating the benefits of probiotics in enhancing exercise performance and verifying the role of the gut–muscle axis. In our previous study, Lactobacillus plantarum PL-02 improved exercise performance and muscle mass. Therefore, the purpose of this study was to investigate whether supplementation with PL-02 combined with resistance training has a synergistic effect on exercise performance and muscle mass. All the animals were assigned into four groups (n = 8/group): a sedentary control with normal distilled water group (vehicle, n = 8); PL-02 supplementation group (PL-02, 2.05 × 109 CFU, n = 8); resistance training group (RT, n = 8); PL-02 supplementation combined with resistance training group (PL-02 + RT, 2.05 × 109 CFU, n = 8). Supplementation with PL-02 for four consecutive weeks combined with resistance exercise training significantly improved the grip strength and the maximum number of crawls; increased the time of exhaustive exercise; significantly reduced the time required for a single climb; and reduced the lactate, blood ammonia, creatine kinase, and blood urea nitrogen produced after exercise (p < 0.05). In addition, it produced substantial benefits for increasing muscle mass without causing any physical damage. In summary, our findings confirmed that PL-02 or RT supplementation alone is effective in improving muscle mass and exercise performance and in reducing exercise fatigue, but the combination of the two can achieve increased benefits.